Regulation of basement membrane-reactive B cells in BXSB, (NZBxNZW)F1, NZB, and MRL/lpr lupus mice. (May 2013) - Clark, Amy G.; Fan, Qihua; Brady, Graham F.; Mackin, Katherine M.; Coffman, Evan D.; Weston, Melissa L.; Foster, Mary H.
<x xml:space="preserve">Abstract</x> Autoantibodies to diverse antigens escape regulation in systemic lupus erythematosus under the influence of a multitude of predisposing genes. To gain insight into the differential impact of diverse genetic backgrounds on tolerance mechanisms controlling autoantibody production in lupus, we established a single lupus-derived nephritis associated anti-basement membrane Ig transgene on each of four inbred murine lupus strains, including BXSB, (NZBxNZW)F1, NZB, and MRL/lpr, as approved by the Duke University and the Durham Veterans Affairs Medical Centers' Animal Care and Use Committees. In nonautoimmune C57BL/6 mice, B cells bearing this anti-laminin Ig transgene are stringently regulated by central deletion, editing, and anergy. Here, we show that tolerance is generally intact in unmanipulated Ig transgenic BXSB, (NZBxNZW)F1, and NZB mice, based on absence of serum transgenic anti-laminin autoantibodies and failure to recover spontaneous anti-laminin monoclonal antibodies. Four- to six-fold depletion of splenic B cells in transgenic mice of these strains, as well as in MRL/lpr transgenic mice, and reduced frequency of IgM+ bone marrow B cells suggest that central deletion is grossly intact. Nonetheless the 4 strains demonstrate distinct transgenic B cell phenotypes, including endotoxin-stimulated production of anti-laminin antibodies by B cells from transgenic NZB mice, and in vitro hyperproliferation of both endotoxin- and BCR-stimulated B cells from transgenic BXSB mice, which are shown to have an enrichment of CD21-high marginal zone cells. Rare anti-laminin transgenic B cells spontaneously escape tolerance in MRL/lpr mice. Further study of the mechanisms underlying these strain-specific B cell fates will provide insight into genetic modification of humoral autoimmunity in lupus.